Walk hard : the Dewey Cox story - Kasdan, Jake, 1975-; Apatow, Judd, 1968-; Townsend, Clayton; Reilly, John C., 1965-; Fischer, Jenna, 1974-; Barry, Raymond J., 1939-; Columbia Pictures; Relativity Media; Copyright Collection (Library of Congress) (United States : Columbia Pictures, 2007)
The up-and-down and then up-again story of musician Dewey Cox, who eventually earns the love of a good woman, longtime backup singer Darlene.
Copyright Claimant: GH Three LLC. Columbia Pictures Industries, Inc. PREV: 2006, PAu 3-075-988. Pre-existing Material: Previously published musical compositions and sound recordings of compositions. Previously published artwork and photography. Screenplay previously registered. Date of Creation: 2007; Date of Publication: December 20, 2007; Registration Number / Date: PA0001590420 / 2007-12-20.
Summary adapted from Internet movie database, viewed Mar. 19, 2008.
Not viewed.
Sources used: copyright database; Variety Web site, review posted Dec. 14, 2007, viewed Mar. 19, 2008; Internet movie database, viewed Mar. 19, 2008; FirstSearch, OCLC 191854196, viewed Mar. 19, 2008.
Executive producer, Lew Morton ; camera, Uta Briesewitz ; editing, Tara Timpone, Steve Welch ; music, Michael Andrews.
John C. Reilly, Jenna Fischer, Raymond J. Barry, Kristen Wiig, Tim Meadows, Harold Ramis, Margo Martindale, Chris Parnell, Matt Besser.
Keywords: Musicians -- Drama; Drug addicts -- Drama; Rock music -- Drama; Man-woman relationships -- Drama; Comedy -- Feature; Musical -- Feature